Naloxegol (Movantik®) Provides Rapid and Sustained Improvement of Opioid-Induced Constipation Symptoms Irrespective of Opioid Dose - McLeskey, Charles; Gudin, Jeffrey; Adler, Jeremy; Rockett, Carol; Jamindar, Mansi; Rauck, Richard; Webster, Lynn; Mallick-Searle, Theresa (Pain management nursing, 2023)
Naloxegol (Movantik), an oral peripherally acting mu-opioid receptor antagonist has demonstrated rapid relief of opioid-induced constipation (OIC) in patients with chronic non-cancer pain in two phase 3 trials (KODIAC 4/5; NCT01309841/NCT01323790). This analysis aims to characterize the OIC symptom burden and evaluate the efficacy of naloxegol in treating symptoms of OIC based on daily opioid dosages. This is the first naloxegol analysis based on a lower opioid dose cutoff of 100 MEU/day. Data were pooled from the KODIAC 4/5 intent-to-treat populations (N=1337). Subjects treated with placebo (PBO) and naloxegol (12.5mg, 25mg) QD were evaluated based on opioid dose ranges (lower dose, ≤100mg; higher dose, >100mg MEU/day). OIC symptoms assessed include number of spontaneous bowel movements (SBM/wk), complete evacuation (CSBM), straining (scale 1=not at all, 5=extreme) and stool consistency (Bristol Stool Scale: 1=hard, 7=watery). Baseline OIC symptom burden (SBM/wk, CSBM/wk, straining, stool consistency) was similar between lower (n=764) and higher (n=567) opioid dose subgroups. Naloxegol (12.5mg, 25mg) provided significant improvement vs PBO in SBMs/wk in the lower and higher opioid dose subgroups; ≤100 MEU (mean SBM/wk: 2.41, 2.91 vs 1.99, respectively; p<0.05) and ˃100 MEU (mean SBM/wk: 2.81, 3.53 vs 2.05, respectively; p< 0.05). A significant improvement in CSBMs/wk vs PBO was demonstrated in the lower dose subgroup for naloxegol 25mg (mean CSBM/wk: 1.48, 1.97 vs 1.38; p=0.54 and p<0.05, respectively) and in the higher dose subgroup for both naloxegol regimens (mean CSBM/wk: 1.90, 2.36 vs 1.20, respectively; p<0.05). In both dose subgroups, rapid symptom improvement in SBM, CSBM and stool consistency were seen within the first week with naloxegol (p<0.05). Regardless of opioid dose, naloxegol (12.5mg, 25mg) provided rapid and sustained improvement of clinically relevant OIC symptoms. These data suggest that all patients should routinely be assessed for OIC, as lower opioid doses often induce constipation.